The Role of Organizational Commitment in Mediating the Effects of Job Promotion and the Work Environment on Employee Performance - Luckhy N.A. Lotte; Louis Soemadi Bopeng; Rosalia Monika Tahoba (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to analyze the effects of job promotions and the work environment on employee performance, with organizational commitment serving as a mediating variable, at the Manokwari Regency Education Office. Research Method: This study employed a quantitative approach with an explanatory research design. The sample consisted of 56 civil servants (ASN) selected through saturation sampling. Data were collected using a questionnaire, supplemented by observations, interviews, and documentation, and were then analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4. Results and Discussion: The work environment has a positive and significant effect on organizational commitment and employee performance. Organizational commitment also positively affects employee performance and partially mediates the relationship between the work environment and employee performance. Conversely, job promotions do not have a significant effect on either organizational commitment or employee performance. Implications: Improving the quality of the work environment is more effective than job promotions in strengthening organizational commitment and employee performance. Originality: Improving the quality of the work environment is more effective than job promotions in strengthening organizational commitment and employee performance.